Revenues Analysis Of Textile Fabric Araneae As Innovation High Quality - Rizky Ramadhan; Aanja Rahyuni Silalahi; Zakaria Ecep; Adinda Nursabilla Purba (JASc (Journal of Agribusiness Sciences), 2019)
Spiders (Araneae) are predatory animals that are sometimes cannibal, they eat their own species even though the main prey is insects. Almost all types of spiders can inject poison through a pair of fangs. Even so, of the tens of thousands of species of spiders that exist, only about 200 species are equipped with poisons that are harmful to humans ‘. Araneae fabrics are the latest innovations made from unique materials. We are interested in conducting this study, citing a study by someone who said "The team of chemists from ASU learned that the molecular structure of the fiber could produce the latest technology in making materials such as vests, bulletproof to artificial tendons.          The purpose of this research is to make spiders as a work of new innovations of high-quality fabrics, opening new jobs for the community, able to meet market needs, affordable prices can be felt by fabric lovers. This research is used as a momentum to attract unique and interesting spider fiber communities.The methods used in making this cloth are as follows; The initial steps that must be done are to collect the main raw materials and KANARA supporting materials, then after the tools and materials have been fulfilled, they can immediately carry out the production process beginning with the spider taken from the silk fiber, dyed with dye and chemical liquid after that spinning Using a spinning tool that will produce yarn and then the thread is sewn and formed of cloth until it is produced a fabric product made of spider webs.Fabric Operating Revenues, namely Revenue of Rp. 20,580,000 reduced by a total cost of Rp. 12,500,000 per 70 meters so as to obtain revenues of Rp. 18,280,000.